ASSOCIATION OF ZINGIBER AROMATICUM VAL. WITH ZERUMBONE AND ITS BIOLOGICAL ACTIVITY: A LITERATURE REVIEW - Murwanti, Retno; Pratiwi, Rima Dwi; Gani, Andayana Puspitasari (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
The main objective of this article is to explore the available classified information on Zingiber aromaticum Val. Rhizome and its active compound, Zerumbone. Throughout history, this plant has been utilized to treat various ailments such as abdominal disorders, cough, anemia, malaria, jaundice, arthritis, and infections. Recently, Zerumbone, a sesquiterpene compound found in the rhizomes, has gained attention for its biological activity. This article reviews the current research on the pharmacological activities of Z. aromaticum Val. Rhizome, with a specific focus on its active component, Zerumbone.This review found that the antioxidant and antiinflammatory effects of Zerumbone play a role in the pharmacological effects exhibited by Z. aromaticum, such as antidiabetic, antiparasitic, anti-hyperlipidemia, antianxiety, and antiaging effects. Additionally, the correlation between the biological activity of Zerumbone and the pharmacological activity of Z. aromaticum extract is discussed. This review provides a valuable reference for developing and further researching Zingiber aromaticum Val. and Zerumbone in medical treatments.